Associations of lipid levels during gestation with hypertensive disorders of pregnancy and gestational diabetes mellitus: a prospective longitudinal cohort study. Issue 12 (23rd December 2016) - Shen, Hong; Liu, Xiaohua; Chen, Yan; HE, Biwei; Cheng, Weiwei
Abstract : Objective: To assess associations of elevated lipid levels during gestation with hypertensive disorders of pregnancy (HDP) and gestational diabetes mellitus (GDM). Methods: This prospective cohort study was conducted in a tertiary maternal hospital in Shanghai, China from February to November 2014. Lipid constituents, including triglycerides (TGs), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-c) and high-density lipoprotein cholesterol (HDL-c) of 1310 eligible women were assessed in the first (10–13+ weeks), second (22–28 weeks) and third (30–35 weeks) trimesters consecutively. Associations of lipid profiles with HDP and/or GDM outcomes were assessed. Results: Compared with the normal group, maternal TG concentrations were higher in the HDP/GDM groups across the three trimesters (p<0.001); TC and LDL-c amounts were only higher in the first trimester for the HDP and GDM groups (p<0.05). HDL-c levels were similar in the three groups. Compared with intermediate TG levels (25–75th centile), higher TG amounts (>75th centile) were associated with increased risk of HDP/GDM in each trimester with aORs (95% CI) of 2.04 (1.41 to 2.95), 1.81 (1.25 to 2.63) and 1.78 (1.24 to 2.54), respectively. High TG elevation from the first to third trimesters (>75th centile) was associated with increased risk of HDP, with an aOR of 2.09 (1.16 to 3.78). High TG elevation before 28 weeks was associated with increased risk of GDM, with an aOR of 1.67 (1.10 to 2.54). TG elevation was positively correlated with weight gain during gestation (R=0.089, p=0.005). Conclusions: Controlling weight gain during pregnancy could decrease TG elevation and reduce the risk of HDP/GDM. TGs could be used as follow-up parameters during complicated pregnancy, while other lipids are meaningful only in the first trimester.